Cosmology - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
If you find the concept of Dark Matter to be intriguing, watch the Cosmology Episode of Matter and Beyond, where we explore how the new cosmology and how new astronomical discoveries are changing the way we view the universe and our selves. Dr. Joel Primack, Nancy Abrams and Dr. Priya Natarajan shares their insights.
Executive producer, Nasuhi yurt.
Host : MaryLynn Schiavi.
Keywords: Cosmology